Image compression using wavelet transform - Yong, Choon Fon. (2009)
Wavelet, an elegant mathematical tool, is fast gaining the interest of professionals and researchers in many related fields of signal processing. It is fast replacing Fourier and other traditional methods in solving problems of signal processing, unifying some intuitively similar perspectives in this arena, such as filter bank theory, multiresolution analysis and subband coding, among others. Instead of the multitude of traditional tools and techniques, wavelets offer us a simple and efficient tool as a replacement.